2017
DOI: 10.12659/msm.902536
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Baicalin on Blood Pressure and Left Ventricular Remodeling in Rats with Renovascular Hypertension

Abstract: BackgroundThis study aimed to explore the effect of baicalin, which is a kind of bioactive flavonoid, on blood pressure and left ventricular remodeling in rats with renovascular hypertension.Material/MethodsA total of 40 male Wistar rats were randomly assigned into sham-operation (n=10) and renal hypertension model groups (2-kidney-1 clip; 2K-1C, n=30). The rats in the renal hypertension model group were randomly subdivided into 2K-1C (n=13) and 2K-1C/Baicalin groups (n=14). The cardiac function indexes were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
3
14
0
Order By: Relevance
“…BAI, along with its metabolite baicalein have many targets and may have protective effects on diverse diseases. The previous studies found that BAI had effects on neuroprotective, renovascular hypertension, cancer, obesity, and liver dysfunction (Dai et al, 2017;Sowndhararajan et al, 2018;Tang et al, 2016;Xi et al, 2015). However, it has been unclear that the effects and mechanisms of BAI on PD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…BAI, along with its metabolite baicalein have many targets and may have protective effects on diverse diseases. The previous studies found that BAI had effects on neuroprotective, renovascular hypertension, cancer, obesity, and liver dysfunction (Dai et al, 2017;Sowndhararajan et al, 2018;Tang et al, 2016;Xi et al, 2015). However, it has been unclear that the effects and mechanisms of BAI on PD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertensive heart disease is one of the most common complications and can lead to death in hypertensive patients. Therefore, it is an important strategy to improve ventricular remodelling and to prevent hypertensive heart disease for the reduction of the morbidity and mortality of hypertensive patients …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is an important strategy to improve ventricular remodelling and to prevent hypertensive heart disease for the reduction of the morbidity and mortality of hypertensive patients. [19,20] In this study, we examined the function of left ventricular at the 18, 22 and 26 weeks of age in SHRs. The results showed that the LVPW became thickened with age in the SHR group, while the EF and FS decreased, indicating that SHRs exhibited ventricular remodelling and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Baicalin has been widely studied in several in vitro and in vivo models and showed many activities such as: anti-viral [42], anti-oxidative via several pathways [43], neuroprotective and enhancin cognitive functions [44,45], anti-inflammatory [46], anti-cancer [47,48], and hepatoprotection [49]. In recent years, many studies showed anti-hypertensive properties of baicalin [46,[50][51][52][53][54][55][56][57][58][59][60], and also cardioprotective [50], antiplatelet, anticoagulant, and profibrinolytic activities [61].…”
Section: Influence In Pregnancymentioning
confidence: 99%
“…On the other hand, studies in rats with renovascular hypertension showed that baicalin (2 ml of 100 mg/kg baicalin i.p. for 4 weeks once a day) has no significant antihypertensive effect [52]. Baicalein (aglycon of baicalin) protected against hypertension associated with diabetes and showed decrease of vascular deleterious effects associated with both insulin deficiency (ID) and insulin resistance (IR) models.…”
Section: In Vivo Studies Related To the Various Models Of Hypertensionmentioning
confidence: 99%